Application of Marketing Mix in Home Industry: Focussed on Micro and Small-Scale Coffee Industries - Lya Aklimawati; Djoko Soemarno; Surip Mawardi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Differences  in  marketing  strategies  with  other  industries  are  needed  to maintain  business  sustainability  especially  for  facing  fierce  market  competition. This  research  was  aimed  to  identify  a  marketing  mix  implemented  in  micro  and small  scale  coffee  industries,  and  to  identify  external  factors  that  affected  business sustainability.  This  study  was  carried  out  in  Sumberwringin  Sub-district, Bondowoso  District,  East  Java.  Respondents  of  this  study  were  25  coffee  industry players  selected  by  using  judgement  sampling  method.  Primary  and  secondary data  were  collected  in  this  study.  Data  were  analyzed  with  descriptive-qualitative method  and  interactive  analysis.  The  results  showed  that  micro  and  small-scale coffee industries was still implementing conventional  marketing pattern. The marketing mix  which  applied  in  coffee  industry,  were  (a)  the  product  mix  was  not  persistent that  depended  on  consumer  demand;  (b)  selling  price  of  product  was  determined from  cost  production  and  profit  margins;  (c)  distribution  was  conducted  with active  and  passive  marketing  particularly  based  on  customer  orders;  (d)  promotion mix  was  implemented  by  direct  marketing,  personal  selling,  and  word  of  mouth. Micro-environments of the marketing affecting micro and small-scale coffee industries were: (a) customers as main target market  in form  of consumer markets and  alternative target  market  as  re-seller  markets;  (b)  high  intensity  competition  as  a  result of  large  number of  competitors  and  lack  of  product  diversification;  (c)  many  raw material suppliers, but expensive  input  production  cost; (d) there was no a marketing partnership  with  marketer  agent/other  partner,  but  it  had  strategic  partnership with  supplier  and  government;  (e)  government  policies  on  product  development and  marketing  had  been  implemented  by  facilitating  exhibition  activity,  processing equipment,  and  training.